Linear accelerator radiosurgery for arteriovenous malformations: Updated literature review. (April 2017) - Yahya, S.; Heyes, G.; Nightingale, P.; Lamin, S.; Chavda, S.; Geh, I.; Spooner, D.; Cruickshank, G.; Sanghera, P.
Highlights: Patient selection criteria for intervention remains controversial in the management of arteriovenous malformations (AVM) in light of recent studies. Despite inherent differences in the dose metrics and prescription methods across radiosurgery platforms, a comprehensive review of clinical outcomes is unable to conclude that any one platform offers a superior clinical outcom. Abstract: Arteriovenous malformations (AVMs) are the leading causing of intra-cerebral haemorrhage. Stereotactic radiosurgery (SRS) is an established treatment for arteriovenous malformations (AVM) and commonly delivered using Gamma Knife within dedicated radiosurgery units. Linear accelerator (LINAC) SRS is increasingly available however debate remains over whether it offers an equivalent outcome. The aim of this project is to evaluate the outcomes using LINAC SRS for AVMs used within a UK neurosciences unit and review the literature to aid decision making across various SRS platforms. Results have shown comparability across platforms and strongly supports that an adapted LINAC based SRS facility within a dynamic regional neuro-oncology department delivers similar outcomes (in terms of obliteration and toxicity) to any other dedicated radio-surgical platform. Locally available facilities can facilitate discussion between options however throughput will inevitably be lower than centrally based dedicated national radiosurgery units.